2013
DOI: 10.1007/s00540-013-1660-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clonidine added to lidocaine for sub-Tenon’s (episcleral) anesthesia in cataract surgery

Abstract: The addition of clonidine 1 μg/kg to 2 % lidocaine in sub-Tenon's anesthesia for cataract surgery increased the duration of sensory anesthesia, ocular akinesia, and the duration of analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several studies have shown favorable results of opioids the combination with local drugs, such as lidocaine and fentanyl, in increasing the effect and depth of local anesthesia. In the study of Cabral et al on local anesthesia for cataract surgery, adding clonidine to lidocaine for subtenon anesthesia increased the duration of anesthesia and immobilization of the eye and analgesia (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown favorable results of opioids the combination with local drugs, such as lidocaine and fentanyl, in increasing the effect and depth of local anesthesia. In the study of Cabral et al on local anesthesia for cataract surgery, adding clonidine to lidocaine for subtenon anesthesia increased the duration of anesthesia and immobilization of the eye and analgesia (11).…”
Section: Discussionmentioning
confidence: 99%
“…The final anesthetic solution volume was 6 mL, and the doses of lidocaine and clonidine used were based on previous studies. 11 , 18 , 22 Patients were monitored with electrocardiogram, Mean Arterial Pressure (MAP), Heart Rate (HR), and Oxygen Saturation (SpO 2 ), preoperatively. A 22G intravenous catheter in the upper limb was used for peripheral venous access of infusion of 0.9% sodium chloride solution.…”
Section: Methodsmentioning
confidence: 99%
“…Clonidine is a central and peripheral α2 adrenergic receptor agonist. It has been used as an adjuvant during regional ophthalmic anesthesia due to its analgesic properties 16 with potentiation of motor and sensory blocks, 17 , 18 , 19 , 20 , 21 , 22 as well as IOP reduction. 17 , 21 Studies, however, were performed to assess the quality of anesthesia and did not assess the effects of clonidine on ocular hemodynamics in ophthalmic blocks.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of clonidine 1 μg/kg to 2 % lidocaine in sub-Tenon's anesthesia for cataract surgery increased the duration of sensory anesthesia, ocular akinesia, and the duration of analgesia [15] .…”
Section: Sub-tenon's Anaesthesiamentioning
confidence: 99%